Unilateral flail chest is seldom a lethal injury. Issue 12 (27th November 2006) - Borman, J B; Aharonson-Daniel, L; Savitsky, B; Peleg, K
Abstract : Background: The chest cage is a common target for traumatic damage. Although relatively rare, it is considered to be a serious condition with significant reported mortalities. As most flail injuries are accompanied by severe extrathoracic injuries, it is often difficult to pinpoint a single injury responsible for the patient's death. Aim: To investigate the factors related to mortality when flail injury is diagnosed. Methods: Data from the Israel National Trauma Registry between 1998 and 2003 included 11 966 chest injuries (262 flail chest injuries) out of a total of 118 211 trauma hospitalisations. Mortality figures were analysed to determine which factors, singly or in combination, influenced flail chest mortality. Results: Road crashes accounted for most flail injuries (76%). The total mortality was 54 (20.6%) of 262 patients with flail chest injuries. 13 (20.4%) of the deaths occurred soon after admission to the emergency room and 37 (68.5%) within the first 24 h. Mortality in moderate to severe injuries (injury severity score (ISS) 9–24) was 3.6% and that in critical injuries 28.5% (ISS >24). Mortality increased with age: 17% in those aged <45 years, 22.1% in those between 45 and 64 years and 28.8% in those >65 years. Age remained a risk for inpatient death when adjusted for severity. Mortality in isolated unilateral flail injury was not more than 6%. Total mortality for traumatic brain injury (TBI) and flail was 34%. Flail, TBI and other major injuries increased the mortality to 61.1%. Conclusions: Advanced age is associated with higher mortality. Isolated unilateral bony cage instability infrequently leads to death in patients who make it to the emergency department but rather its combination with additional extrathoracic trauma.